Mobile app development for EEE MSc student connectivity and exploration of NTU - Tan, Gail Ling Ern (Nanyang Technological University, 2023)
The master programs of NTU EEE is usually conducted over a short duration of one year for full-time students. During this period, most graduate students will face difficulties such as navigating camp and making new friends. These difficulties may feel larger for international students who have not explored the university campus and have not formed any prior connections with other graduates in NTU EEE.